Maternal experience of fetal movements from a child with AMC: MECA survey - Arduç, Arda; Linskens, Ingeborg H.; Dussa, Chakravarthy U.; van Bosse, Harold; Lemin, Sara; Sawatzky, Bonita; Filges, Isabel; De Vries, Johanna I.P. (Early Human Development, 2025)
Objective: The prevailing assumption is that fetal movements are always absent or reduced in pregnancies affected by arthrogryposis multiplex congenita (AMC), leading to the belief that mothers do not perceive or perceive less fetal movements during affected pregnancies. This study aims to investigate the maternal perception of fetal movements in pregnancies with a child diagnosed with AMC and to challenge this assumption. Additionally, it seeks to expand current knowledge on the perception by comparing with pregnancies with children not affected by AMC. Methods: A survey-based study was conducted in collaboration with international patient support groups. The survey included mothers with at least one child diagnosed with AMC. The questionnaire covered not only the presence of movements, but also other aspects such as daily movements, consistency throughout the pregnancy, and perceived normalcy. A subgroup comparison was made between mothers who had both an affected and non-affected pregnancy, as well as by pregnancy order and its impact on clinical follow-up. Results: A total of 170 mothers participated in this survey and 118 (70 %) of them had both an affected and non-affected pregnancy and 52 (30 %) had pregnancies with AMC-affected children alone. Most (77 %) perceived fetal movements during AMC-affected pregnancies, though fewer described them as daily (66 %), stable (51 %), or normal (44 %) compared to unaffected pregnancies. Conclusion: This study showed that fetal movements can be perceived by the majority of mothers of children with AMC. The presence of fetal movements should not rule out the possibility of AMC in case of fetal contractures.
CRIS-Team Scopus Importer:2025-06-13
Keywords: Arthrogryposis multiplex congenita; Fetal movements; Maternal experience; Perception